An SDN-Based Framework for E2E QoS Guarantee in Internet of Things Devices - Ali, Jehad; Song, Houbing Herbert; Roh, Byeong Hee (IEEE Internet of Things Journal, 2025)
—In 5G and Beyond-based Internet of Things (IoT) sensor networks, the end-to-end (E2E) route traverses via multiple heterogeneous network domains, necessitating interdomain interaction to guarantee and confirm Quality-of-Service (QoS) for low-power IoT devices applications. Moreover, in heterogeneous IoT sensor networks, the E2E path often encompasses domains with diverse QoS parameters or classes. The unique E2E requirements for delay, packet loss ratio (PLR), and other factors present further challenges. However, existing legacy network architectures and typical software-defined networking (SDN) models lack effective strategies for QoS provisioning tailored to the service requests of IoT low-power sensor devices. To address these issues, this study proposes a novel multiobjective SDN-based framework for IoT sensors, ensuring E2E QoS across multiple domains with heterogeneous traffic service classes (TSC). A two-layer SDN framework is presented to provision QoS for IoT sensors based on their specific service demands at the E2E network level. Central to the framework is the deployment of an optimal additive weighting module (OAWM), facilitating TSC ranking according to their weights and incorporating a priority mechanism for specific service parameters, such as delay, PLR, and jitter. Additionally, the global controller statistics enable the provisioning of E2E QoS by mapping the service requests from IoT sensors. Experimental evaluations are conducted to compare the proposed approach with existing schemes. The results validate the effectiveness of our proposed method, demonstrating improved E2E QoS provisioning and meeting the specific requirements of IoT sensors in precision agriculture with low-power IoT devices.
Keywords: Intelligent networking; Intelligent networking architecture; Low Power; Networking architecture; Packet loss ratio; Precision Agriculture; Quality-of-service; Sensors network; Service class; Software-defined networkings; Intelligent networking architecture; Internet of Things (IoT); precision agriculture; Quality-of-Service (QoS); software-defined networking (SDN)